2021
DOI: 10.3847/1538-4357/abcc72
|View full text |Cite
|
Sign up to set email alerts
|

FIR-luminous [C ii] Emitters in the ALMA-SCUBA-2 COSMOS Survey (AS2COSMOS): The Nature of Submillimeter Galaxies in a 10 Comoving Megaparsec-scale Structure at z ∼ 4.6

Abstract: witsuhshiD sF nd wtsudD F nd milD sn nd rytsuD xFrF nd impsonD tFwF nd winnkD eFwF nd mehtD rF nd hudzevi© ut eD F nd firkinD tFiF nd skrshiD F nd ghenD ghinEghou nd dkiD uF nd jimD rF nd rrikneD F nd snmiD rF nd ghpmnD FgF nd rtsukdeD fF nd sonoD hF nd funkerD eF nd eoD F nd itoD F nd edD tF nd kmotoD F @PHPIA 9psEluminous g ss imitters in the evweEgfeEP gywy urvey @ePgywyAX he xture of umillimeter qlxies in IH gomoving wegprseEsle truture t z ∼RFTF9D he estrophysil tournlD WHU @PAF pF IPPF

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 112 publications
2
10
0
Order By: Relevance
“…To investigate whether there is a specific property that explains its Planck significant detection, we compare G237 with other protoclusters situated in the Cosmos field at z∼2-2.5. There are other protoclusters found at much higher redshifts (e.g., Capak et al 2011;Pavesi et al 2018;Lemaux et al 2018;Mitsuhashi et al 2021), but we do not analyze them as the Planck high-z source selection is not tailored to find protoclusters at z 4.…”
Section: Structure Properties That Make a Planck High-z Sourcementioning
confidence: 99%
“…To investigate whether there is a specific property that explains its Planck significant detection, we compare G237 with other protoclusters situated in the Cosmos field at z∼2-2.5. There are other protoclusters found at much higher redshifts (e.g., Capak et al 2011;Pavesi et al 2018;Lemaux et al 2018;Mitsuhashi et al 2021), but we do not analyze them as the Planck high-z source selection is not tailored to find protoclusters at z 4.…”
Section: Structure Properties That Make a Planck High-z Sourcementioning
confidence: 99%
“…These ALMA-detected H-faint galaxies, found in abundance (∼530 deg −2 by Wang et al 2019), are proposed as a critical tracer of the early phase of massive galaxy formation history. However, most of their physical properties still remain highly uncertain except for rare cases with spectroscopic confirmations (e.g., Walter et al 2012;Wang et al 2019;Umehata et al 2020;Zhou et al 2020;Caputi et al 2021;Mitsuhashi et al 2021) due to their non-detections and faintness at most wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…To determine redshifts, the target SMGs are grouped into three categories; SMGs with multiple line detection, those with only one line detection, and then finally those that do not have emission line detection. Other work in the literature are referenced to aid the redshift determinations, in particular those from Jiménez-Andrade et al ( 2020) and Mitsuhashi et al (2021). The category to which each SMG belongs is given in Table 2.…”
Section: Redshift Determinationmentioning
confidence: 99%
“…Simpson et al (2020) andMitsuhashi et al (2021) both reported the redshift of AS2COS0001.2 to be 4.635±0.001 based on the CII line.…”
mentioning
confidence: 99%